5.4.8 Problems 701 to 800

Table 5.429: Second ODE homogeneous ODE

#

ODE

Mathematica

Maple

7674

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}-\frac {y}{x^{2}} = 0 \]

7675

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}-\frac {y}{x^{2}} = 0 \]

7676

\[ {}\left (3 x -1\right )^{2} y^{\prime \prime }+\left (9 x -3\right ) y^{\prime }-9 y = 0 \]

7677

\[ {}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 0 \]

7678

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

7679

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

7680

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

7681

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

7682

\[ {}y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

7684

\[ {}x^{2} y^{\prime \prime }-2 y = 0 \]

7685

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

7686

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

7697

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+\alpha ^{2} y = 0 \]

7698

\[ {}y^{\prime \prime }-2 x y^{\prime }+2 \alpha y = 0 \]

7699

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 0 \]

7700

\[ {}2 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

7701

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

7705

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+5 y = 0 \]

7706

\[ {}x^{2} y^{\prime \prime }+\left (-2-i\right ) x y^{\prime }+3 i y = 0 \]

7761

\[ {}y y^{\prime \prime }+4 {y^{\prime }}^{2} = 0 \]

7762

\[ {}y^{\prime \prime }+k^{2} y = 0 \]

7763

\[ {}y^{\prime \prime } = y y^{\prime } \]

7766

\[ {}y^{\prime \prime } = -\frac {1}{2 {y^{\prime }}^{2}} \]

7767

\[ {}y^{\prime \prime }+\sin \left (y\right ) = 0 \]

7768

\[ {}y^{\prime \prime }+\sin \left (y\right ) = 0 \]

7777

\[ {}y^{\prime \prime }+4 y = 0 \]

7778

\[ {}y^{\prime \prime }-4 y = 0 \]

7804

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = 0 \]

7905

\[ {}y y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

7906

\[ {}x y y^{\prime \prime } = {y^{\prime }}^{3}+y^{\prime } \]

7907

\[ {}y^{\prime \prime }-k^{2} y = 0 \]

7908

\[ {}x^{2} y^{\prime \prime } = 2 x y^{\prime }+{y^{\prime }}^{2} \]

7910

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = 0 \]

7912

\[ {}\left (x^{2}+2 y^{\prime }\right ) y^{\prime \prime }+2 x y^{\prime } = 0 \]

7913

\[ {}y y^{\prime \prime } = y^{\prime } y^{2}+{y^{\prime }}^{2} \]

7914

\[ {}y^{\prime \prime } = y^{\prime } {\mathrm e}^{y} \]

7933

\[ {}y y^{\prime \prime }-{y^{\prime }}^{2} = 0 \]

7934

\[ {}x y^{\prime \prime } = y^{\prime }-2 {y^{\prime }}^{3} \]

7935

\[ {}y y^{\prime \prime }+y^{\prime } = 0 \]

7937

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

7938

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

7939

\[ {}y^{\prime \prime }+8 y = 0 \]

7940

\[ {}2 y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

7941

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

7942

\[ {}y^{\prime \prime }-9 y^{\prime }+20 y = 0 \]

7943

\[ {}2 y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

7944

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

7945

\[ {}y^{\prime \prime }+y = 0 \]

7946

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

7947

\[ {}4 y^{\prime \prime }+20 y^{\prime }+25 y = 0 \]

7948

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = 0 \]

7949

\[ {}y^{\prime \prime } = 4 y \]

7950

\[ {}4 y^{\prime \prime }-8 y^{\prime }+7 y = 0 \]

7951

\[ {}2 y^{\prime \prime }+y^{\prime }-y = 0 \]

7952

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7953

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7954

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 0 \]

7955

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

7956

\[ {}y^{\prime \prime }-6 y^{\prime }+5 y = 0 \]

7957

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

7958

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 0 \]

7959

\[ {}y^{\prime \prime }+4 y^{\prime }+2 y = 0 \]

7960

\[ {}y^{\prime \prime }+8 y^{\prime }-9 y = 0 \]

7961

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+10 y = 0 \]

7962

\[ {}2 x^{2} y^{\prime \prime }+10 x y^{\prime }+8 y = 0 \]

7963

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-12 y = 0 \]

7964

\[ {}4 x^{2} y^{\prime \prime }-3 y = 0 \]

7965

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0 \]

7966

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-6 y = 0 \]

7967

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }+3 y = 0 \]

7968

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-2 y = 0 \]

7969

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-16 y = 0 \]

8005

\[ {}y^{\prime \prime }+y = 0 \]

8006

\[ {}y^{\prime \prime }-y = 0 \]

8007

\[ {}x y^{\prime \prime }+3 y^{\prime } = 0 \]

8008

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

8009

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

8010

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

8011

\[ {}y^{\prime \prime }-\frac {x y^{\prime }}{x -1}+\frac {y}{x -1} = 0 \]

8012

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

8013

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

8014

\[ {}y^{\prime \prime }-x f \left (x \right ) y^{\prime }+f \left (x \right ) y = 0 \]

8015

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

8039

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

8040

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

8041

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

8042

\[ {}y^{\prime \prime }-y^{\prime }+6 y = 0 \]

8047

\[ {}y^{\prime \prime }+9 y = 0 \]

8067

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

8070

\[ {}y^{\prime \prime } = -3 y \]

8071

\[ {}y^{\prime \prime }+\sin \left (y\right ) = 0 \]

8177

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = 0 \]

8219

\[ {}y^{\prime \prime }+y = 0 \]

8221

\[ {}y^{\prime \prime }-y = 0 \]

8223

\[ {}y^{\prime \prime }-y^{\prime } = 0 \]

8225

\[ {}y^{\prime \prime }+2 y^{\prime } = 0 \]

8287

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{9}\right ) y = 0 \]

8288

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

8289

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-25\right ) y = 0 \]

8290

\[ {}16 x^{2} y^{\prime \prime }+16 x y^{\prime }+\left (16 x^{2}-1\right ) y = 0 \]